Integration of radioactive, conventional logs and geochemical analyses to evaluate the hydrocarbon system of Rudeis Formation, October oil field, Gulf of Suez, Egypt - Marwa Z. EL-SAWY; Ibrahim M. AL-ALFY; Sherif FAROUK; Tarek F. SHAZLY; Nouran S. SALAMA (Contributions to Geophysics and Geodesy, 2025)
The objective of this research is to determine the source rock by using a combination of well logging data, spectral gamma-ray logs, as well as laboratory geochemical analysis. This involves quantifying the total organic carbon content (TOC) as a key parameter to study the source rock of Rudeis Formation rocks in the October oil field, Gulf of Suez, Egypt. After theoretical calculations of well logging, the mean TOC value comes out to 1.2 wt%. The TOC values in the lab ranged from 0.4 wt% to 1.4 wt%, with a mean value of 0.9 wt%. According to Rudeis Formation's petrophysical properties, the hydrocarbon saturation levels in the upper and lower Rudeis reservoirs were recorded 57% to 60%, and the percentages of shale content in each reached 63% and 51%, respectively. The Radiogenic Heat Production (RHP) values ranged from 0.85 μW/m3 (minimum) to 2.38 μW/m3 (maximum) with a mean of 1.37 μW/m3 and a standard deviation of approximately 0.19 μW/m3. Five sections along the Rudeis Formation (Source 1 to Source 5) are considered hydrocarbon-bearing zones. Three of the zones were classified as source rocks (Source 2, Source 3, and Source 5) associated with a high volume of shales (mostly clay), while the other two zones (Source 1 and Source 4) are associated with a moderate volume of shales (shaly sandstones) considered to be source and reservoir rocks in the Upper and Lower Rudeis Formation. The lower Rudeis unit appears to have fair to good hydrocarbon potential, with TOC ranging from 0.46 to 1.28 weight percent and S2 varying from 0.88 to 3.76 mg/g. The upper Rudeis member is classified as a fair oil source rock, based on TOC values ranging from 0.42 to 1.29%. The equations (1), (2) and (3) were found to be the best fit to the TOC data.